A mathematical model for facility location in banking industry - Amir Ehsani; Abolfazl Danaei; Mohammad Hemmati (Management Science Letters)
This paper presents an empirical investigation to determine the efficient locations of bank branch as well as automated banking machine. The study develops a mathematical model to minimize the cost of facility establishment subject to some constraints, which are associated with the population, accessibility of facilities, etc. All input parameters are considered in terms of triangular fuzzy numbers and using some methods, they numbers are converted into crisp values. The method has been applied for four cities in province of Seman, Iran and using WinQSB, the efficient locations of the facilities for a private bank named Samen have been determined.